CO2 epoxy coupling catalyst as well as preparation method and application thereof

By grafting the bissulfonic acid-based ionic liquid and metal halide salt on the surface of multi-stage pore UiO-66-NH2, a stable Lewis acid-base active center is formed, which solves the problem of poor structural stability of ionic liquids in the catalysis of CO2 and epoxy compounds. , improves catalytic activity and reusable performance, simplifies the separation process and reduces operating costs.

CN119259117APending Publication Date: 2025-01-07HENAN POLYTECHNIC UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411384155.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing ionic liquids have poor structural stability in the coupling catalysis of CO2 and epoxy compounds, and the catalytic effect is fast weakened, making it difficult to meet the reusable needs, and the separation and purification process is complex.

Method used

The multi-stage pore UiO-66-NH2 surface of Zr4+ coordination defect is grafted with a bisulfonic acid-based ionic liquid and introduced metal halide salt to form a bifunctional catalyst with a Lewis acid-base active center, by forming [-NH3]+[-SO3 ]-Chemical bond stabilizes the bissulfonic acid-based ionic liquid, combined with metal halides to form a stable catalyst.

Benefits of technology

It improves the structural stability and catalytic activity of the catalyst, extends the service life of the catalytic effect, simplifies the separation and recovery process, reduces the operating cost, and meets the catalytic demand for coupling CO2 and epoxy compounds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259117A_ABST
    Figure CN119259117A_ABST
Patent Text Reader

Abstract

The invention discloses a CO2 epoxy coupling catalyst as well as a preparation method and application thereof. The CO2 epoxy coupling catalyst is prepared by grafting disulfonic ionic liquid on the surface of Zr < 4 + > coordination defect hierarchical pore UiO-66-NH2 and introducing metal halide salt. The preparation method comprises the following steps: S1, preparing and synthesizing Zr < 4 + > coordination defect hierarchical pore UiO-66-NH2; s2, enabling the hierarchical pore UiO-66-NH2 to react and combine with the disulfonic ionic liquid, so as to obtain an ILs (at) UiO-66-NH2 compound; and S3, reacting and combining the ILs-coated UiO-66-NH2 compound with metal halide salt, and drying to obtain the CO2 epoxy coupling catalyst. The CO2 epoxy coupling catalyst can be applied to a coupling reaction of CO2 and an epoxy compound to synthesize cyclic carbonate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material preparation, and in particular to a CO2 epoxide coupling catalyst and a preparation method and application thereof. Background Art

[0002] As a homogeneous catalyst composed of anions and cations, ionic liquids have relatively low melting and boiling points, can be well integrated with reactants and products, show relatively high catalytic activity in chemical reactions, and can effectively promote the coupling process of CO2 and epoxides; and, under mild conditions, when ionic liquids are used alone as catalysts, the reaction can also proceed efficiently. However, it is relatively difficult to separate homogeneous ionic liquids from the reaction system, and the subsequent product purification process is also relatively complicated.

[0003] It is reported that the metal nodes of MOFs can serve as Lewis acid sites, and nitrogen-containing organic ligands generally have the ability to enhance base-catalyzed reactions. Therefore, by integrating ionic liquids with MOFs, the advantages of multiple materials can be combined to achieve the desired dual-functional properties. However, most researchers only introduce ionic liquids into MOFs cages. During use, the ionic liquids are continuously leached out, the catalytic effect weakens rapidly, the structural stability is poor, and there is almost no reusability, which makes it difficult to meet the coupling catalytic needs of CO2 and epoxides. It is necessary to improve them. Summary of the invention

[0004] The object of the present invention is to provide a CO2 epoxide coupling catalyst with a stable structure and improved catalytic effect, and a preparation method and application thereof in view of the above problems.

[0005] In order to achieve the above object, the technical solution of the present invention is:

[0006] A CO2 epoxide coupling catalyst, wherein the CO2 epoxide coupling catalyst is 4+ The coordination-defective hierarchical porous UiO-66-NH2 surface is grafted with disulfonic acid ionic liquid and introduced with metal halide.

[0007] A method for preparing a CO2 epoxide coupling catalyst comprises the following steps:

[0008] S1, the template (1-10 mL), zirconium chloride (0.1-1 mmol), 2-aminoterephthalic acid and organic acid (0.5-5 mL) with the same amount of zirconium chloride were dissolved in the first organic solvent (30-70 mL) in sequence, and the reaction was carried out at a temperature of 120-160°C for 18-48 hours to synthesize Zr 4+ Multi-level pores of coordination defects UiO-66-NH2;

[0009] S2, disperse the multi-level porous UiO-66-NH2 (0.05-0.5 g) in the second organic solvent (30-100 mL), then add the disulfonic acid ionic liquid (0.1-1 g), and stir well; heat to 60-120 ° C and react for 6-24 hours to allow the disulfonic acid ionic liquid to diffuse into the pores of the multi-level porous UiO-66-NH2 and form ionic bonds ([-NH3] + [-SO3] - ), after cooling, washing away the excess bissulfonic acid ionic liquid with a second organic solvent, and drying to obtain an ILs@UiO-66-NH2 composite;

[0010] S3. Disperse the ILs@UiO-66-NH2 complex (0.1-1 g) in a second organic solvent (30-100 mL), then add a metal halide (0.2-2 g), heat to 90-150°C and react for 4-12 hours; after the reaction, centrifuge and wash to remove excess metal halide, and dry to obtain an ionic liquid complex coupled with UiO-66-NH2 bifunctional catalyst (ILs-M@UiO-66-NH2) as a CO2 epoxide coupling catalyst.

[0011] Furthermore, in step S1, the volume ratio of the template, zirconium chloride, 2-aminoterephthalic acid, organic acid, and the first organic solvent is 1-10:1-10:1-10:5-50:30-70.

[0012] Furthermore, in step S1, the template is polystyrene microspheres, and the particle size thereof is 10 to 80 nm.

[0013] Furthermore, in step S1, the organic acid is a mixture of one or more of lauric acid, myristic acid, caprylic acid, formic acid, and acetic acid.

[0014] Furthermore, in step S1, the first organic solvent is a mixture of one or more of dimethylformamide, dimethylacetamide, acetonitrile and tetrahydrofuran.

[0015] Furthermore, in step S2 and step S3, the second organic solvent is a mixture of one or more of methanol, ethanol, n-propanol, and isopropanol.

[0016] Furthermore, the disulfonic acid ionic liquid is [C3BSim]Cl, [C3BSim]Br, [BSim]Cl,

[0017] A mixture of one or more of [BSim]Br and [BSim]I; the molecular formula structure of [C3BSim]Cl is The molecular formula of [C3BSim]Br is The molecular formula of [BSim]Cl is The molecular formula of [BSim]Br is The molecular formula of [BSim]I is

[0018] Furthermore, in step S2, the metal halide salt is a mixture of one or more of FeCl3, MnCl2, MnBr2, CoCl2, NiCl2, ZnCl2, ZnBr2, ZnI2, CuCl2, CdCl2, CdBr2, and CdI2.

[0019] The invention discloses an application of a CO2 epoxide coupling catalyst, wherein the CO2 epoxide coupling catalyst can be applied to the coupling reaction of CO2 and an epoxy compound to synthesize cyclic carbonate.

[0020] Furthermore, the epoxy compound is a mixture of one or more of propylene oxide, epichlorohydrin, butylene oxide, styrene oxide, cyclohexene oxide, and allyl glycidyl ether.

[0021] Compared with the prior art, the present invention has the following advantages and positive effects:

[0022] The present invention synthesizes multi-level porous Zr 4+ The coordination defective UiO-66-NH2 is then introduced into the disulfonic acid ionic liquid and metal halide salt to form [-NH3] + [-SO3] -The chemical bond bridges the bissulfonic acid ionic liquid to the molecular structure of UiO-66-NH2, and then the metal halide and the ionic liquid are coordinated to form a bifunctional catalytic material in which the ionic liquid complex bridges UiO-66-NH2; the bifunctional catalytic material has a Lewis acid-base active center, which can coordinate the catalyst CO2 with the epoxide coupling reaction; in the catalyst, UiO-66-NH2 has a rich pore structure and a large specific surface area, which can effectively adsorb and activate epoxides, and the bissulfonic acid ionic liquid complex grafted on the surface of UiO-66-NH2 can effectively adsorb and activate CO2, and is in an activated state Epoxides and CO2 can be efficiently converted into cyclic carbonates. The combination of the two has higher catalytic activity and can effectively improve the catalytic effect of the coupling of CO2 and epoxides. Moreover, the grafting of disulfonic acid ionic liquids onto MOFs can form a stable lattice structure, which ensures the structural stability of the catalyst and reduces the rate of weakening of the catalytic effect during use, which can fully meet the catalytic needs of the coupling of CO2 and epoxides. At the same time, the catalyst can be separated and recovered by simple operation after the catalytic reaction is completed, and its reusability is high, thereby effectively reducing the operating cost of the coupling reaction of CO2 and epoxides, and has excellent market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0024] Figure 1 This is the X-ray diffraction pattern of multi-level pore UiO-66-NH2;

[0025] Figure 2 This is a scanning electron microscope image of multi-level pore UiO-66-NH2;

[0026] Figure 3 This is a scanning electron microscope image of the bissulfonic acid ionic liquid [C3BSim]Cl coupled with multi-level porous UiO-66-NH2;

[0027] Figure 4 It is a schematic diagram of the molecular structure of the catalyst in the present invention. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work, any modifications, equivalent substitutions, improvements, etc., should be included in the protection scope of the present invention.

[0029] Example 1. This example discloses a CO2 epoxide coupling catalyst, which is a Zr 4+ The UiO-66-NH2 bifunctional catalyst (ILs-M@UiO-66-NH2) was coupled with a bissulfonate ionic liquid complex prepared by grafting a bissulfonate ionic liquid on the surface of the coordination-defective hierarchical porous UiO-66-NH2 and introducing a metal halide.

[0030] The steps of preparing the catalyst are as follows:

[0031] (1) Synthesis of hierarchical pore UiO-66-NH2;

[0032] First, 1 mL of polystyrene microspheres (particle size of 10 nm), 0.1 mmol of zirconium chloride, 0.1 mmol of 2-aminoterephthalic acid, and 0.5 mL of lauric acid were dissolved in 30 mL of dimethylformamide in sequence, and subjected to hydrothermal reaction at 120 ° C for 18 h to synthesize a Zr 4+ Multi-level pores of coordination defects UiO-66-NH2;

[0033] (2) Synthesize disulfonic acid ionic liquid complexes to couple UiO-66-NH2;

[0034] (a) 0.05 g of the synthesized hierarchical UiO-66-NH2 was dispersed in 30 mL of methanol, and then 0.1% of the bissulfonic acid ionic liquid ([C3BSim]Cl) was added, stirred evenly, and reacted at 60 °C for 6 h to allow the bissulfonic acid ionic liquid to diffuse into the pores of the hierarchical UiO-66-NH2 and form ionic bonds ([-NH3] + [-SO3] - ), after cooling, the excess bissulfonic acid ionic liquid was washed away with methanol, and the ILs@UiO-66-NH2 composite was obtained after drying;

[0035] (b) 0.1 g of ILs@UiO-66-NH2 complex was dispersed in 30 mL of methanol, and then 0.2 g of FeCl3 was added and reacted at 90 °C for 4 h. After the reaction, the excess FeCl3 was removed by centrifugation and washed, and the bifunctional catalyst (ILs-M@UiO-66-NH2) of the bissulfonic acid ionic liquid complex coupled with UiO-66-NH2 was obtained after drying.

[0036] The catalyst can be applied to the coupling reaction of CO2 and propylene oxide to synthesize cyclic carbonate.

[0037] Example 2: This example discloses a CO2 epoxide coupling catalyst, which is a Zr 4+ The UiO-66-NH2 bifunctional catalyst (ILs-M@UiO-66-NH2) was coupled with a bissulfonate ionic liquid complex prepared by grafting a bissulfonate ionic liquid on the surface of the coordination-defective hierarchical porous UiO-66-NH2 and introducing a metal halide.

[0038] The steps of preparing the catalyst are as follows:

[0039] (1) Synthesis of hierarchical pore UiO-66-NH2;

[0040] First, 5 mL of polystyrene microspheres (particle size of 30 nm), 0.5 mmol of zirconium chloride, 0.5 mmol of 2-aminoterephthalic acid, and 2 mL of myristic acid were dissolved in 50 mL of dimethylacetamide in sequence, and subjected to hydrothermal reaction at 140 °C for 36 h to synthesize Zr 4+ Multi-level pores of coordination defects UiO-66-NH2;

[0041] (2) Synthesize disulfonic acid ionic liquid complexes to couple UiO-66-NH2;

[0042] (a) 0.2 g of the synthesized hierarchical UiO-66-NH2 was dispersed in 50 mL of ethanol, and then 0.5 g of bissulfonic acid ionic liquid ([C3BSim]Br) was added, stirred evenly, and reacted at 80 °C for 12 h to allow the bissulfonic acid ionic liquid to diffuse into the pores of the hierarchical UiO-66-NH2 and form ionic bonds ([-NH3] + [-SO3] - ), after cooling, the excess bissulfonic acid ionic liquid was washed away with ethanol, and the ILs@UiO-66-NH2 composite was obtained after drying;

[0043] (b) 0.5 g of ILs@UiO-66-NH2 complex was dispersed in 60 mL of ethanol, and then 1 g of MnCl2 was added and reacted at 120 °C for 8 h. After the reaction, the excess MnCl2 was removed by centrifugation and washed, and the bifunctional catalyst (ILs-M@UiO-66-NH2) of the bissulfonic acid ionic liquid complex coupled with UiO-66-NH2 was obtained after drying.

[0044] The catalyst can be applied to the coupling reaction of CO2 and epichlorohydrin to synthesize cyclic carbonate.

[0045] Example 3: This example discloses a CO2 epoxide coupling catalyst, which is a Zr 4+ The UiO-66-NH2 bifunctional catalyst (ILs-M@UiO-66-NH2) was coupled with a bissulfonate ionic liquid complex prepared by grafting a bissulfonate ionic liquid on the surface of the coordination-defective hierarchical porous UiO-66-NH2 and introducing a metal halide.

[0046] The steps of preparing the catalyst are as follows:

[0047] (1) Synthesis of hierarchical pore UiO-66-NH2;

[0048] First, 10 mL of template (particle size 80 nm), 1 mmol of zirconium chloride, 1 mmol of 2-aminoterephthalic acid, and 5 mL of acetic acid were dissolved in 70 mL of tetrahydrofuran, and subjected to hydrothermal reaction at 160 ° C for 48 h to synthesize a Zr 4+ Multi-level pores of coordination defects UiO-66-NH2;

[0049] (2) Synthesize disulfonic acid ionic liquid complexes to couple UiO-66-NH2;

[0050] (a) 0.5 g of the synthesized hierarchical UiO-66-NH2 was dispersed in 100 mL of isopropanol, and then 1 g of bissulfonic acid ionic liquid ([BSim]Cl) was added, stirred thoroughly, and reacted at 120 °C for 24 h to allow the bissulfonic acid ionic liquid to diffuse into the pores of the hierarchical UiO-66-NH2 and form ionic bonds ([-NH3] + [-SO3] - ), after cooling, the excess bissulfonic acid ionic liquid was washed away with isopropanol, and the ILs@UiO-66-NH2 composite was obtained after drying;

[0051] (b) 1 g of ILs@UiO-66-NH2 complex was dispersed in 100 mL of isopropanol, and then 2 g of CdI2 was added and reacted at 150 °C for 12 h. After the reaction, the excess CdI2 was removed by centrifugation and washed, and the bifunctional catalyst (ILs-M@UiO-66-NH2) of the bissulfonic acid ionic liquid complex coupled with UiO-66-NH2 was obtained after drying.

[0052] The catalyst can be applied to the coupling reaction of CO2 and allyl glycidyl ether to synthesize cyclic carbonate.

[0053] The bifunctional catalyst of the present invention is verified by several test examples below;

[0054] Test Example 1: Preparation of a bifunctional catalyst of bissulfonic acid ionic liquid complex coupled with UiO-66-NH2;

[0055] (1) Synthesis of multi-level porous UiO-66-NH2; The X-ray diffraction pattern of multi-level porous UiO-66-NH2 is shown in Figure 1 As shown, the scanning electron microscope image of multi-level pore UiO-66-NH2 is as follows Figure 2 As shown;

[0056] First, 5 mL of polystyrene microspheres with a particle size of 30 nm, 0.5 mmol of zirconium chloride, 0.5 mmol of 2-aminoterephthalic acid, and 2 mL of lauric acid were dissolved in 50 mL of dimethylformamide in sequence, and subjected to hydrothermal reaction at 120 ° C for 24 h to synthesize Zr 4+ Multi-level pores of coordination defects UiO-66-NH2;

[0057] (2) Synthesize disulfonic acid ionic liquid complexes to couple UiO-66-NH2;

[0058] (a) 0.2 g of the synthesized hierarchical UiO-66-NH2 was dispersed in 50 mL of methanol, and then 0.3 g of disulfonic acid ionic liquid ([C3BSim]Cl) was added and stirred thoroughly. The mixture was then reacted at 60 °C for 6 h to allow the ionic liquid to diffuse into the hierarchical UiO-66-NH2. 2的 The pores form ionic bonds ([-NH3] + [-SO3] - ), after cooling, the excess bissulfonic acid ionic liquid was washed off with methanol, and after drying, an ILs@UiO-66-NH2 complex was obtained; the ILs@UiO-66-NH2 complex was formed by coupling the bissulfonic acid ionic liquid [C3BSim]Cl with UiO-66-NH2 having multi-level pores, and its scanning electron microscopy image is shown in Figure 3 As shown;

[0059] (b) 0.3 g of ILs@UiO-66-NH2 complex was dispersed in 40 mL of ethanol, and then 0.5 g of MnCl2 was added and reacted at 120 °C for 6 h. After the reaction, the excess metal salt was removed by centrifugation and washing, and the bifunctional catalyst (ILs-M@UiO-66-NH2) of the bissulfonic acid ionic liquid complex coupled with UiO-66-NH2 was obtained after drying. The molecular structure of the bifunctional catalyst of the bissulfonic acid ionic liquid complex coupled with UiO-66-NH2 is shown in the figure. Figure 4 shown.

[0060] Test Example 2:

[0061] The preparation steps and methods are the same as those of Experimental Example 1, except that the polystyrene microspheres with a particle size of 30 nm in step (1) of Experimental Example 1 are replaced with polystyrene microspheres with a particle size of 50 nm.

[0062] Test Example 3:

[0063] The preparation steps and method were the same as those of Experimental Example 1, except that 2 mL of lauric acid in step (1) of Experimental Example 1 was replaced with 4 mL of lauric acid.

[0064] Test example 4:

[0065] The preparation steps and methods are the same as those of Experimental Example 1, except that the bissulfonic acid ionic liquid [C3BSim]Cl introduced in step (2) of Experimental Example 1 is replaced by the bissulfonic acid ionic liquid [C3BSim]Br.

[0066] Test Example 5:

[0067] The preparation steps and methods are the same as those of Experimental Example 1, except that the disulfonic acid ionic liquid [C3BSim]Cl introduced in step (2) of Experimental Example 1 is replaced by the disulfonic acid ionic liquid [C3BSim]Br, and the metal halide MnCl2 is replaced by the metal halide MnBr2.

[0068] Test Example 6:

[0069] The preparation steps and methods are the same as those of Experimental Example 1, except that the metal halide salt MnCl2 introduced in step (2) of Experimental Example 1 is replaced by the metal halide salt NiCl2.

[0070] Catalytic performance evaluation

[0071] The activity of the catalysts prepared in Test Examples 1-6 was compared using epichlorohydrin as the reaction substrate. The reaction conditions were as follows: epichlorohydrin and 1.0% by weight of the catalyst were added to a 50 ml stainless steel reactor, which was sealed and washed with CO2 for 3 times. CO2 was then charged again to make the initial gas pressure reach 2.5 MPa, and then the temperature was raised to the set temperature. After reacting for 8 hours, the reactor was quickly cooled to room temperature with ice water, the reaction mixture was taken out, and the organic liquid without the catalyst was obtained by centrifugation, and gas phase analysis was performed with ethylene glycol butyl ether as the internal standard; the catalysts in Test Examples 1-6 were tested for catalytic CO2 and epichlorohydrin, and the test results are shown in Table 1.

[0072] Table 1 Comparison of catalytic activity of CO2 and epichlorohydrin in the conversion of cyclic carbonates in Experimental Examples 1-6

[0073] serial number Epichlorohydrin conversion rate (wt%) Cyclocarbonic acid selectivity (wt%) Reaction temperature (℃) <![CDATA[UiO-66-NH2]]> 17.9 98.6 90 Test Example 1 81.9 98.3 90 Test Example 2 83.1 98.7 90 Test Example 3 86.6 98.2 90 Test Example 4 91.3 99.3 90 Test Example 5 93.8 99.1 90 Test Example 6 70.8 98.8 90

[0074] From the data in Table 1, it can be seen that in the catalysts prepared in Experimental Examples 1-6, the catalytic activity of promoting the coupling reaction of CO2 and epichlorohydrin is significantly improved after the multi-level porous UiO-66-NH2 is bridged with the disulfonic acid ionic liquid complex. This is mainly because the nitrogen-containing groups in the bridged disulfonic acid ionic liquid complex have Lewis basicity and are compatible with Zr in the multi-level porous UiO-66-NH2. 4+ The Lewis acidity presented constitutes a synergistic catalytic center, which has the functions of adsorption and activation of CO2 and epichlorohydrin, and insertion and ring closure of activated intermediates. Therefore, bridging the disulfonic acid ionic liquid complex on the surface of the hierarchical pore UiO-66-NH2 can enrich the Lewis acid-alkalinity in the structure and improve the catalytic activity of a single material.

[0075] The present invention synthesizes multi-level porous Zr 4+ The coordination defective UiO-66-NH2 is then introduced into the disulfonic acid ionic liquid and metal halide salt to form [-NH3] + [-SO3] -The chemical bond bridges the bissulfonic acid ionic liquid to the molecular structure of UiO-66-NH2, and then the metal halide and the ionic liquid are coordinated to form a bifunctional catalytic material in which the ionic liquid complex bridges UiO-66-NH2; the bifunctional catalytic material has a Lewis acid-base active center, which can coordinate the catalyst CO2 with the epoxide coupling reaction; in the catalyst, UiO-66-NH2 has a rich pore structure and a large specific surface area, which can effectively adsorb and activate epoxides, and the bissulfonic acid ionic liquid complex grafted on the surface of UiO-66-NH2 can effectively adsorb and activate CO2, and is in an activated state Epoxides and CO2 can be efficiently converted into cyclic carbonates. The combination of the two has higher catalytic activity and can effectively improve the catalytic effect of the coupling of CO2 and epoxides. Moreover, the grafting of disulfonic acid ionic liquids onto MOFs can form a stable lattice structure, which ensures the structural stability of the catalyst and reduces the rate of weakening of the catalytic effect during use, which can fully meet the catalytic needs of the coupling of CO2 and epoxides. At the same time, the catalyst can be separated and recovered by simple operation after the catalytic reaction is completed, and its reusability is high, thereby effectively reducing the operating cost of the coupling reaction of CO2 and epoxides, and has excellent market application prospects.

Claims

1. A CO2 epoxide coupling catalyst, characterized in that: The CO2 epoxide coupling catalyst is prepared by 4+ The coordination-defective hierarchical porous UiO-66-NH2 surface is grafted with disulfonic acid ionic liquid and introduced with metal halide.

2. A method for preparing a CO2 epoxide coupling catalyst as claimed in claim 1, characterized in that: The following steps are involved: S1, dissolve the template, zirconium chloride, 2-aminoterephthalic acid, and organic acid in the first organic solvent in sequence, and perform hydrothermal reaction at a temperature of 120 to 160°C for 18 to 48 hours to synthesize Zr 4+ Multi-level pores of coordination defects UiO-66-NH2; S2, dispersing the hierarchical UiO-66-NH2 in a second organic solvent, then adding the disulfonic acid ionic liquid, and stirring well; heating to 60-120° C. and reacting for 6-24 hours, so that the disulfonic acid ionic liquid diffuses into the pores of the hierarchical UiO-66-NH2 and forms ionic bonds with the amino groups on the hierarchical UiO-66-NH2 skeleton; after cooling, washing away the excess disulfonic acid ionic liquid with the second organic solvent, and obtaining the ILs@UiO-66-NH2 complex after drying; S3. Disperse the ILs@UiO-66-NH2 complex in a second organic solvent, then add a metal halide, heat to 90-150° C. and react for 4-12 hours. After the reaction is completed, remove excess metal halide by centrifugation and washing, and obtain a CO2 epoxide coupling catalyst after drying.

3. The method for preparing a CO2 epoxide coupling catalyst as claimed in claim 2, characterized in that: In the step S1, the template is polystyrene microspheres, and the particle size thereof is 10 to 80 nm.

4. The method for preparing a CO2 epoxide coupling catalyst as claimed in claim 2, characterized in that: In step S1, the organic acid is a mixture of one or more of lauric acid, myristic acid, caprylic acid, formic acid, and acetic acid.

5. The method for preparing a CO2 epoxide coupling catalyst according to claim 2, characterized in that: In the step S1, the first organic solvent is a mixture of one or more of dimethylformamide, dimethylacetamide, acetonitrile and tetrahydrofuran.

6. The method for preparing a CO2 epoxide coupling catalyst according to claim 2, characterized in that: In step S2 and step S3, the second organic solvent is a mixture of one or more of methanol, ethanol, n-propanol, and isopropanol.

7. The method for preparing a CO2 epoxide coupling catalyst according to claim 2, characterized in that: In step S2, the bissulfonic acid ionic liquid is a mixture of one or more of [C3BSim]Cl, [C3BSim]Br, [BSim]Cl, [BSim]Br, and [BSim]I; the molecular formula structure of [C3BSim]Cl is The molecular formula of [C3BSim]Br is The molecular formula of [BSim]Cl is The molecular formula of [BSim]Br is The molecular formula of [BSim]I is 8. The method for preparing a CO2 epoxide coupling catalyst as claimed in claim 2, characterized in that: In step S2, the metal halide salt is a mixture of one or more of FeCl3, MnCl2, MnBr2, CoCl2, NiCl2, ZnCl2, ZnBr2, ZnI2, CuCl2, CdCl2, CdBr2, and CdI2.

9. A use of the CO2 epoxide coupling catalyst as claimed in claim 1, characterized in that: The CO2-epoxy coupling catalyst can be applied to the coupling reaction of CO2 and epoxy compounds to synthesize cyclic carbonates.

10. The use of the CO2 epoxide coupling catalyst as claimed in claim 9, characterized in that: The epoxy compound is a mixture of one or more of propylene oxide, epichlorohydrin, butylene oxide, styrene oxide, cyclohexene oxide and allyl glycidyl ether.

Citation Information

Cited By

  • Production method of LC-grade diethyltoluenediamine

    CN119841734A

  • A kind of production method of LC grade diethyltoluenediamine

    CN119841734B